1992
DOI: 10.1111/j.1467-8624.1992.tb01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Bilingual Children's Receptive Vocabularies

Abstract: Receptive vocabulary of Hispanic children in Miami was tested in both English and Spanish with complementary standardized tests, the Peabody Picture Vocabulary Test (PPVT-R) and the Test de Vocabulario en Imágenes Peabody (TVIP-H). 105 bilingual first graders, of middle to high socioeconomic status relative to national norms, were divided according to the language(s) spoken in their homes. Both groups, whether they spoke only Spanish in the home (OSH) or both English and Spanish in the home (ESH), performed ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 13 publications
8
108
1
Order By: Relevance
“…For ELL children, these different contexts additionally occur in different languages. Thus, the situation specific language that children learn may be encoded in two different languages (Pearson and Fernández 1994; Peña et al 2002; Umbel et al 1992). If the teacher does not speak the home language and the parent does not speak the school language it is more critical to gather information from multiple sources.…”
Section: Discussionmentioning
confidence: 99%
“…For ELL children, these different contexts additionally occur in different languages. Thus, the situation specific language that children learn may be encoded in two different languages (Pearson and Fernández 1994; Peña et al 2002; Umbel et al 1992). If the teacher does not speak the home language and the parent does not speak the school language it is more critical to gather information from multiple sources.…”
Section: Discussionmentioning
confidence: 99%
“…Bilingual children have repeatedly been found to score below their monolingual peers (e.g., Ben-Zeev, 1977; Bialystok, Luk, Peets, & Yang, 2010; Hemsley, Holm, & Dodd, 2006; Leseman, 2000) or below monolingual norms (e.g., Fernandez, Pearson, Umbel, Oller, & Molinetmolina, 1992; Mancilla-Martinez et al, 2011; Teoh et al, 2012; Uccelli & Paez, 2007; Uchikoshi, 2006; Umbel, Pearson, Fernandez, & Oller, 1992) on single-language vocabulary measures in one or both of their languages. Oller and colleagues (2007) highlight the distributed nature of lexical knowledge in bilinguals as a key contributor to their lower single-language vocabulary scores when compared to monolinguals.…”
Section: The Monolingual-bilingual Gap On Single-language Vocabulary mentioning
confidence: 99%
“…In the United States, it is a demographic reality that bilingual children from immigrant families often have lower SES than their monolingual peers and than the children included in the standardization samples for test norms (e.g., Mancilla-Martinez et al, 2011; Uccelli & Paez, 2007; Umbel & Oller, 1994). However, some studies that have controlled for SES have still found vocabulary discrepancies between bilingual and monolingual children (e.g., Fernandez et al, 1992; Hemsley et al, 2006; Leseman, 2000; Umbel & Oller, 1994; Umbel et al, 1992). When conceptual scoring was used with parent checklists to examine the vocabulary growth of Spanish-English bilingual toddlers from low-SES homes, their conceptual scores were below both English and Spanish monolingual norms (Mancilla-Martinez & Vagh, 2013).…”
Section: Factors Influencing the Vocabulary Performance Of Bilingual mentioning
confidence: 99%
“…Umbel, Pearson, Fernández, & Oller, 1992 showed that, for 105 first-grade children who spoke Spanish and English, "learning two languages at once does not harm receptive language development in the language of origin" (p. 1012). They indicated that children's receptive vocabulary consisted of a significant number of words that did not overlap in both languages.…”
Section: Multilingual Statusmentioning
confidence: 97%
“…Studies that consider the impact of multilingualism on typically developing children's speech and language acquisition have shown that when skills in both languages are considered, children who speak more than one language are not at greater risk for speech and language impairment than monolingual children (De Houwer, 2009;Goldstein & Bunta, 2012;Goldstein & McLeod, 2012;Hambly, Wren, McLeod, & Roulstone, 2013;Umbel, Pearson, Fernández, & Oller, 1992). Umbel, Pearson, Fernández, & Oller, 1992 showed that, for 105 first-grade children who spoke Spanish and English, "learning two languages at once does not harm receptive language development in the language of origin" (p. 1012).…”
Section: Multilingual Statusmentioning
confidence: 98%